RESPON DAN TINGKAT ADOPSI PETANI TERHADAP PROGRAM CORPORATE FARMING DI DESA TRIMULYO KABUPATEN BANTUL, DIY - Ismiasih, Ismiasih; Winda Adnanti, Mega; Yusuf, Ilma Fatimah (JURNAL AGRIBISAINS, 2022)
The entry of new programs or innivations in society will certainly lead to new thoughts or knowledge in attitudes, behavoir in individuals. Thia study aims to determine the implementation of the corporate farming program, the response of farmers to the corporate farming program, and the level of farmer adoption of the corporate farming program in Trimulyo Village, Bantul Regency, DIY. The basic method in this research used a qualitative descriptive method. The research location was determined purposively, in Trimulyo Village, Bantul Regency, DIY which was implementing a corporate farming program. The sample was determined purposively with a total of 30 farmers. Data analysis used descripyive method and Likert scale. The results showed tha the implementation of the corporate farming program was carried out through socialization, consolidation, land preparation, seeding, planting, weeding, irrigation, fertilization, maintenance, and harvesting. The respon of farmer’s to the corporate farming program from a cognitive perspecyive is in the good category, from an affective perpective it is in the agree category and from a conative perspective it is in the medium category. The overall responses is included in the fairly good category. The level of farmer adoption of the corporate farming program is in the medium category.